Evaluation of clinical parameters for predicting hospital stay in neonates - Gaurav Singla; Harmesh Singh Bains; Ravinder Soni (Mashhad University of Medical Sciences, 2015)
Objective: To predict hospital stay by using various clinical parameters at admission.Patients and Methods: This prospective observational study was conducted over a period of one year (Jan - Dec 2010) in a tertiary level teaching hospital in North India. Out of 344 neonates admitted, 41 left against medical advice and were excluded. At time of admission, initial vital signs were noted along with basic information. All neonates were assessed on the basis of clinical parameters and followed up to the discharge/death. Final outcome was noted in terms of total duration of hospital stay in survived and non survived neonates. In the statistical analysis, Odds ratio along with 95% confidence intervals was calculated for each parameter and significant associations (p value ≤ 0.05) were studied. Results: Of 30 clinical variables, 18 were found to be significantly associated with prolonged hospitalization viz more than 7days in survived neonates. These include abnormal heart rate (>160/min or 60/min or